2021
DOI: 10.2106/jbjs.oa.20.00142
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Osteoporosis Management and Secondary Preventative Treatment After Primary Fragility Fractures

Abstract: Background: Fragility fractures are often sentinel events in documenting new cases of osteoporosis. Numerous analyses have demonstrated low rates of adequate osteoporosis evaluation and treatment following primary fragility fractures. The purpose of this study was to quantify the incidence of primary fragility fractures in America and the rates of osteoporosis screening and management before and after fracture. Methods: A retrospective review of the PearlDiver database was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
4
15
0
Order By: Relevance
“… 36 Although screening patients at risk for osteoporosis and giving pharmacological treatment when indicated decreases the risk of proximal humerus fractures by 45%, Ross et al reported these strategies have been initiated in less than 20% of patients after fragility fractures. 41 , 44 …”
Section: Discussionmentioning
confidence: 99%
“… 36 Although screening patients at risk for osteoporosis and giving pharmacological treatment when indicated decreases the risk of proximal humerus fractures by 45%, Ross et al reported these strategies have been initiated in less than 20% of patients after fragility fractures. 41 , 44 …”
Section: Discussionmentioning
confidence: 99%
“…To include fractures caused by lowenergy trauma only, we excluded all events that were likely to have been caused by high-energy events (such as a motor vehicle collision) at the same time these fractures occurred. This methodology of defining fragility fractures using ICD diagnosis codes was based on published works [1,25].…”
Section: Primary and Secondary Study Outcomesmentioning
confidence: 99%
“…Regarding fractures, there are no specific ICD codes for fragility fractures. Therefore, to define fragility fractures as accurately as possible, we used published works that have used the PearlDiver Database [1,25]. Regarding a comparison of patients at low risk versus those at high risk, we are limited in the reporting of intraoperative information; thus, the study is at risk of selection bias.…”
Section: Limitationsmentioning
confidence: 99%
“…Dr. Leopold: Given how ineffective we’ve been in getting patients who’ve had major fractures and other sentinel events screened [7], why do you believe we might have more success if we intervene at the time of elective surgery in this patient population?…”
Section: Take 5 Interview With Savyasachi C Thakkar Md Senior Author ...mentioning
confidence: 99%
“…I'm mindful of how easy it is for patients not to get the care they need and ought to have. Large studies bear out this worry: Most patients who have a fragility fracture do not receive suitable follow-up, screening, or treatment [7]. This happens despite the concept of sentinel events being known since, well, not long after I learned how to walk.…”
mentioning
confidence: 99%